Monosodium Glutamate Alters the Function and Morphology of the Parotid Gland in Sprague Dawley Rats - Roa,Ignacio (Sociedad Chilena de Anatomía, 2020)
SUMMARY: Monosodium glutamate (MSG) is a flavor enhancer widely used in the food industry, with obesogenic properties, in addition to causing alterations in the oral cavity. The aim of the study was to observe the morphofunctional changes in the parotid gland after the administration of MSG in rats. 18 newborn male Sprague Dawley rats were used, divided into three groups (Control group; MSG1 group: 4 mg/g weight of monosodium glutamate, 5 doses, kept for 8 weeks, and MSG2 group: 4 mg/g weight of MSG, 5 doses, kept for 16 weeks). The body mass index (BMI) was calculated, and the salivary flow, pH, a-amylase activity, Na, Cl, K and Ca were analyzed by quantitative analysis. After euthanasia by ketamine/xylazine overdose, parotid volume was analyzed and stereology was performed. MSG administration caused an increase in BMI and a decrease in parotid volume as well as a reduction in salivary flow and pH and an increase in a-amylase activity, also increasing the salivary sodium and chlorine levels. Alterations in the normal stereological parameters of the gland were observed. Exposure to MSG caused morphofunctional alterations at parotid gland.